Going Native: Native XML Database vs. Relational Database - Lazim, Raghad Yaseen; Adzhar, Kamaludin (2012)
Database is a set of logical data elements that related with each other by a mathematical relationship. The success of any database depend on some important things such: Storage procedure - the speed and ease of query - reduce non-useful information - reduce repetition - fixed records - the organization and strategy and so on.Relational databases have been improved for long time to handle such things very high efficiency. However, despite the maturity of relational database products and the Significant growth in computer power over the past years, the projects still fail because of the performance of the relational database used is just not good enough. Anyhow, always there is another way. Mostly it can be faster to store the data permanently and natively in XML to avoid the repeated conversion from relational format to XML format in the application. Because Native XML Database (NXD) provides a powerful environment for the development of web applications based on XQuery and related standards. This paper discusses the need for going native, and the difference between Native XML database and relational database to achieve high level of the performance.